Audit Quality, Firm Characteristics and Real Earnings Management: The Case of Listed Vietnamese Firms - Khanh, Hoang Thi Mai; Khuong, Nguyen Vinh (International Journal of Economics and Financial Issues, 2018)
This study examines the effect of audit quality and firm characteristics on real earnings management of listed companies in Vietnam. Using the measurement of real earnings management of Roychowdhury (2006), we find that firm size has a negative effect on real earnings management while profitability and firm age have positive effects. Notably, there is no difference between big 4 and non-big 4 in diminishing real earnings management in Vietnam. Our results are based on a large sample of 1,687 firm-year observations on listed companies in Vietnam. We used GMM estimator to test our hypotheses. Our findings make a significant contribution to the literature on the effects of audit quality and firm characteristics on real earnings management, especially in emerging markets. Keywords: Real earnings management, emerging markets, audit quality, firm characteristics. JEL Classifications: G14, M41, M42.